TIC et démocratie locale. Considérations empiriques issues de la pratique du budget participatif dans des communes camerounaises - Calvin Minfegue (Tic & Société)
Following various works on uses of ICTs, this paper focuses on their mobilization in local political dynamics in Cameroon. We observed participatory budgeting practices. This analysis first describes the initial introduction of ICTs in participatory budgeting and then details the various uses of ICT in this process. Finally, It discusses these results in the global framework of debates on e-democracy.